MBL2 gene polymorphisms are not related to the occurrence of cerebrovascular disease in sickle cell anemia (Research, Society and Development, 2020)
Objective: This study has as objective to verify whether MBL2 gene polymorphisms are related to the occurrence of cerebrovascular disease (CD) in sickle cell anemia (SCA) patients. Methods: Overall, 259 unrelated SCA patients were enrolled. The patients were divided into three groups: control group, stroke group ad range of risk group. Peripheral blood samples were collected and DNA extraction was performed. All patients were genotyped for exon 1, promoter region -221 and promoter region -550 of MBL2 gene, along with β-globin gene haplotypes. Results: Concerning the genotyping of the MBL2, there was no difference in the frequency of allelic and genotypic variants of the exon 1 and the promoter regions -221 and -550 of the MBL2 gene among the studied groups. Conclusion: Despite the small number of patients, and the lack of association between MBL2 polymorphisms and CD, our study represents an effort to understand the impact of MBL2 polymorphisms in the clinical outcome of patients with SCA.